Bilateral radiation therapy followed by methotrexate‐based chemotherapy for primary vitreoretinal lymphoma. Issue 4 (4th February 2019) - de la Fuente, Macarena I.; Alderuccio, Juan Pablo; Reis, Isildinha M.; Omuro, Antonio; Markoe, Arnold; Echegaray, Jose J.; Davis, Janet L.; Harbour, J. William; Lossos, Izidore S.
Abstract : Primary vitreoretinal lymphoma (PVRL) is a subset of primary CNS lymphoma that presents as isolated ocular disease without brain involvement. Although ocular radiotherapy (RT) is an effective treatment for PVRL, the optimal treatment is uncertain. PVRL may later involve the brain in 56%‐85% of patients. We report on 12 PVRL patients treated with a combination of bilateral RT and a systemic chemotherapy (CT) regimen containing high‐dose methotrexate (M). Ten received RT (30‐40 Gy) followed by CT, one received RT, and one was treated with intravitreal M; all achieved a complete response (CR). Three patients had tumor recurrence in the brain and received CT and one patient relapsed in the eye with a second recurrence in the brain. Three patients achieved CR‐2 remain alive and one died of dementia. One died from recurrent CNS disease. With a median follow of 68 months (range, 17‐154 months), median progression‐free and overall survival have not been reached. Bilateral RT followed by M‐based CT is an effective treatment for reducing CNS progression and prolonging survival.